An SDS-PAGE reverse-phase metaproteomics approach for polar desert and ornithogenic soils - Kristopher Abdullah; Arkadiusz Nawrocki; Daniel Wilkins; Ling Zhong; Dana Z. Tribbia; Martin R. Larsen; Belinda C. Ferrari (Applied Soil Ecology, 2026)

Nutrient washing to amend nitrite accumulation during hydrocarbon remediation of Antarctic soil - Jieyu Liu; Kristopher Abdullah; Sally Crane; Daniel Wilkins; Greg Hince; Tim Spedding; Nathali Machado de Lima; Belinda Ferrari (Polar Biology, 2026)
Nitrogen-based fertilizers are frequently employed in bioremediation to stimulate microbial degradation of hydrocarbon contaminants. At Casey Station, in eastern Antarctica, a urea-based fertilizer was applied to seven engineered biopiles to remediate soils impacted by historic diesel spills. While this treatment enhanced hydrocarbon degradation, it also altered soil chemistry, resulting in elevated concentrations of ammonia and nitrite. If left unmanaged, the reuse of nutrient-enriched soils poses a risk of off-site migration of soluble nitrogen species, potentially impacting adjacent ecosystems. To assess the feasibility of large-scale nutrient removal, we developed and optimized a laboratory-scale soil washing protocol aimed at reducing excess nitrogen in partially remediated soils. Three intensive washing treatments were evaluated, achieving removal of over 60% of water-extractable ammonia and 95% of nitrite. Quantitative PCR was employed to quantify total bacterial abundance (16S rRNA) and key nitrogen cycling functional groups, including ammonia-oxidizing bacteria (amoA), Nitrospira spp. (16S rRNA), and Nitrobacter-like nitrite oxidizers (nxrA). Soil health assessments revealed significant ( p < 0.05) shifts in nitrifying community composition between pre-washed biopile soils and uncontaminated reference soils. Post-washing, bacterial abundances declined in proportion to treatment intensity, with Nitrospira and Nitrobacter spp. exhibiting delayed recovery relative to ammonia oxidizers, suggesting greater sensitivity of nitrite-oxidizing bacteria to washing-induced disturbance. Despite initial nutrient removal, both laboratory and field observations indicated re-accumulation of nitrite, likely driven by residual ammonium. These findings highlight the importance of optimizing nutrient removal strategies to not only reduce contaminants, but to also minimize the impacts from the removal process on the endemic microbial communities.